2017
DOI: 10.22159/ajpcr.2017.v10i3.16547
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Antioxidant and Anti-Inflammatory Properties of Aqueous Extract of Wild Mushrooms Collected From Himachal Pradesh

Abstract: Objective: The objective of this study is to elucidate phytochemical contents, antioxidant, and anti-inflammatory activity of wild mushrooms collected from Himachal Pradesh.Methods: Quantitative analysis of phytochemical constituents was carried out using standard methods while 1,1 diphenylpicrylhydrazyl nitric oxide, hydrogen peroxide-free radical scavenging assay were used to evaluate the antioxidant properties of selected wild mushrooms. Anti-inflammatory capacity of samples was evaluated by human red blood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 19 publications
(23 reference statements)
1
9
0
Order By: Relevance
“…The immune system of all organisms is not sufficient to protect the body against free radicals. Synthetic antioxidants including butylated hydroxytoluene and hydroxyanisole available and consumed have side effects and are thought to be responsible for carcinogenesis and liver damage [ 7 ]. To protect living beings from oxidative damage, naturally occurring antioxidants such as Vitamin A, C, and E, carotenoids, flavonoids, and other simple phenolic compounds are preferred [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…The immune system of all organisms is not sufficient to protect the body against free radicals. Synthetic antioxidants including butylated hydroxytoluene and hydroxyanisole available and consumed have side effects and are thought to be responsible for carcinogenesis and liver damage [ 7 ]. To protect living beings from oxidative damage, naturally occurring antioxidants such as Vitamin A, C, and E, carotenoids, flavonoids, and other simple phenolic compounds are preferred [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…These edible mushrooms appreciated worldwide have been used in traditional medicine for centuries, due to their health-related benefits. In recent research, the anti-oxidative, anti-inflammatory bioactivities, immunostimulatory, anti-tumor and antimicrobial properties were reported [1,2,3]. It was considered that morel’s health benefits were attributed mainly to sugar (polysaccharides) and to various constituents such as compounds, amino acids, important vitamin, fatty, organic acid and mineral profile [2,4].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies reported in the literature pointed put the potential beneficial applications of mushrooms in human dietary, considering that they possess unique nutritional and chemical properties [6][7][8][9]. Researchers revealed that wild edible mushrooms provide an important amount of fiber and proteins together with other valuable components like essential amino acids but in comparison to other food products they have a low fat content and do not contain cholesterol [10][11][12][13][14]. In addition, wild edible mushrooms are recognized as a delicacy, due to their specific flavor and texture, especially in mountain areas where they are widely collected considering that many studies emphasized their important nutritional value and the fact that amino acids found in mushrooms are comparable with those of animal origin [15].…”
Section: Mountain Food Products: Wild Edible Mushroomsmentioning
confidence: 99%